Theodore Stark Wilkinson papers - Wilkinson, Theodore Stark, 1888-1946.
Correspondence, memoranda, diaries, speeches, dispatches, transcripts of radio broadcasts, biographical material, clippings, scrapbook, printed matter, maps, plans, photographs, and other papers relating to Wilkinson's naval career, especially his duties as deputy commander in the South Pacific area (Oceania) and as commander of the U.S. Navy 3rd Amphibious Force. Diary describes operations at Bougainville Island, Papua New Guinea, in the Solomon Islands; Palau; and Leyte Island in the Philippines. Subjects include Wilkinson's years at United States Naval Academy, his aide Paulus P. Powell, life at sea, naval operations against the Japanese, Japanese negotiations for peace and surrender, interactions with allied military personnel, and Wilkinson's tour of duty in Japan after the surrender. Conferences with William F. Halsey are recorded as well as visits by Richard Evelyn Byrd, Raymond Clapper, H. v. Kaltenborn, Henry Cabot Lodge, Carl Mydans, Ogden R. Reid, and Eleanor Roosevelt.
Correspondents include Harold E. Barrowclough, Claude Raymond Branch, Frederick H. Brooke, Robert Bostwick Carney, Aubrey Wray Fitch, George Hudson Fort, Roy S. Geiger, O.W. Griswold, William Frederick Halsey, John R. Hodge, Royal E. Ingersoll, Randall Jacobs, James Kendall, Thomas C. Kinkaid, Alan Goodrich Kirk, C.H. McMorris, Chester W. Nimitz, Lawrence R. Reifsnider, Richmond Kelly Turner, Nathan F. Twining, A.A. Vandegrift, Edward B. Whitman, Catherine Harlow Wilkinson, Ernest Wilkinson, Gulielma Bostick Wilkinson, Hugh M. Wilkinson, and I. Yegorichev.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Naval officer. Nickname: Ping.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Barrowclough, Harold E. -- Correspondence; Branch, Claude Raymond, -- 1886- -- Correspondence; Brooke, Frederick H. -- Correspondence; Byrd, Richard Evelyn, -- 1888-1957.; Carney, Robert Bostwick, -- 1895-1990 -- Correspondence; Clapper, Raymond, -- 1892-1944.; Fitch, Aubrey Wray, -- 1883-1978 -- Correspondence; Fort, George Hudson, -- 1891- -- Correspondence; Geiger, Roy S. -- 1885-1947 -- Correspondence; Griswold, O. W. -- 1886-1959 -- Correspondence; Halsey, William Frederick, -- 1882-1959.; Halsey, William Frederick, -- 1882-1959 -- Correspondence; Hodge, John R. -- 1893- -- Correspondence; Ingersoll, Royal E. -- 1883-1976 -- Correspondence; Jacobs, Randall, -- 1886-1967 -- Correspondence; Kaltenborn, H. v. -- 1878-1965.; Kendall, James -- Correspondence; Kinkaid, Thomas C. -- 1888-1972 -- Correspondence; Kirk, Alan Goodrich, -- 1888-1963 -- Correspondence; Lodge, Henry Cabot, -- 1902-1985.; McMorris, C. H. -- 1890-1954 -- Correspondence; Mydans, Carl; Nimitz, Chester W. -- 1885-1966 -- Correspondence; Powell, Paulus P; Reid, Ogden R. -- 1925-; Reifsnider, Lawrence F. -- Correspondence; Roosevelt, Eleanor, -- 1884-1962.; Turner, Richmond Kelly, -- 1885-1961 -- Correspondence; Twining, Nathan F. -- 1897-1982 -- Correspondence; Vandegrift, A. A. -- 1887-1973 -- Correspondence; Whitman, Edward B. -- Correspondence; Wilkinson, Catherine Harlow -- Correspondence; Wilkinson, Ernest, -- active 1905-1910 -- Correspondence; Wilkinson, Gulielma Bostick -- Correspondence; Wilkinson, Hugh M. -- 1890-1973 -- Correspondence; Yegorichev, I. -- Correspondence; Wilkinson family; Wilkinson family -- Correspondence; United States. -- Navy -- History -- World War, 1939-1945.; United States. -- Navy. -- Amphibious Force, 3rd.; United States Naval Academy; World War, 1939-1945 -- Oceania; World War, 1939-1945 -- Campaigns -- Palau; World War, 1939-1945 -- Campaigns -- Philippines; World War, 1939-1945 -- Campaigns -- Solomon Islands; World War, 1939-1945 -- Naval operations, American; World War, 1939-1945 -- Peace; World War, 1939-1945 -- Japan; Bougainville Island (Papua New Guinea) -- History; Japan -- History -- Allied occupation, 1945-1952.; Leyte Island (Philippines) -- History; Naval officers